2014
DOI: 10.1186/1757-4749-6-27
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of clarithromycin resistant Helicobacter pylori characterizes unidentified variants of multidrug resistant efflux pump genes

Abstract: BackgroundClarithromycin (CLR) is the key drug in eradication therapy of Helicobacter pylori (H. pylori) infection, and widespread use of CLR has led to an increase in primary CLR-resistant H. pylori. The known mechanism of CLR resistance has been established in A2146G and A2147G mutations in the 23S rRNA gene, but evidence of the involvement of other genetic mechanisms is lacking. Using the MiSeq platform, whole-genome sequencing of the 19 clinical strains and the reference strain ATCC26695 was performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
3
41
1
1
Order By: Relevance
“…Consistent with our earlier report, the WGS data in this study had high sequencing coverage, and were of sufficiently high quality to allow detection of SNVs in the H. pylori genome [20]. …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with our earlier report, the WGS data in this study had high sequencing coverage, and were of sufficiently high quality to allow detection of SNVs in the H. pylori genome [20]. …”
Section: Resultssupporting
confidence: 87%
“…Using WGS, we and others detected potential mutations throughout the H. pylori genome and identified variants when sequence changes were present [20, 24, 25]. Here, we used WGS technology to detect novel variants in uncharacterized cag PAI genes associated with H. pylori pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…For other antibiotics, an additivity with SER may be related to an interference with efflux pumps and thus a sensitization of H. pylori to these substances. The participation of efflux pumps in antibiotic resistance of H. pylori has been demonstrated in many studies [65][66][67][68][69][70][71][72][73], while the use of efflux pump inhibitors (carbonyl cyanide m-chlorophenylhydrazone and Phe-Arg-beta-naphthylamide) correlated with an increased sensitivity to antibiotics [66,69,70,73].…”
Section: Discussionmentioning
confidence: 98%
“…Intriguingly, hefC missense mutations were among the several gene mutations in in vitro-selected isolates with high-level resistance to amoxicillin, and the introduction of a mutated allele to the wild type increased resistance (689). Through examining the whole-genome sequences of clarithromycin-resistant isolates, a new study revealed the gene clusters of TolC homologs involved in clarithromycin susceptibility profiles in individual isolates (690). Given the extremely acidic environments where H. pylori colonizes, the effect of this environment on secondary transporters in in vivo antimicrobial resistance remains to be determined.…”
Section: Helicobacter Sppmentioning
confidence: 99%